1994
DOI: 10.1016/0736-5748(94)90004-3
|View full text |Cite
|
Sign up to set email alerts
|

The neurotrophic peptide Org 2766 does not influence the expression of the immediate early gene c‐fos following sciatic nerve crush in the rat

Abstract: The neurotrophic peptide Org 2766 accelerates the regeneration of peripheral nerves. Although the mechanism of action of this neuropeptide is not yet understood, functional, pharmacological, and morphological evidence has demonstrated that Org 2766 exerts its beneficial effect during the early stages of nerve regeneration. The induction of some members of the Immediate Early Gene (IEG) family such as c-jun and c-fos is one of the first molecular events following peripheral nerve damage. The Fos and Jun protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Last, we regularly observed nonneuronal staining clearly “ringing” principal neurons, suggesting that at least some of the activated cells after 6‐OHDA are satellite cells. The finding that 6‐OHDA chronically elevates Fos in what we believe are satellite cells is consistent with the known effects of distal axon injury to chronically elevate Fos protein production in Schwann cells adjacent to the insult (Plantinga et al, 1994); we extend this concept to include satellite cells, the specialized Schwann cells surrounding principal ganglionic neurons. The chronically elevated Fos in these presumed satellite cells following 6‐OHDA is also consistent with the finding that satellite cell protrusions grow into the synaptic cleft following axotomy, finalizing the physical separation of sympathetic ganglionic neurons from their presynaptic innervation (Matthews and Nelson, 1975).…”
Section: Discussionsupporting
confidence: 88%
“…Last, we regularly observed nonneuronal staining clearly “ringing” principal neurons, suggesting that at least some of the activated cells after 6‐OHDA are satellite cells. The finding that 6‐OHDA chronically elevates Fos in what we believe are satellite cells is consistent with the known effects of distal axon injury to chronically elevate Fos protein production in Schwann cells adjacent to the insult (Plantinga et al, 1994); we extend this concept to include satellite cells, the specialized Schwann cells surrounding principal ganglionic neurons. The chronically elevated Fos in these presumed satellite cells following 6‐OHDA is also consistent with the finding that satellite cell protrusions grow into the synaptic cleft following axotomy, finalizing the physical separation of sympathetic ganglionic neurons from their presynaptic innervation (Matthews and Nelson, 1975).…”
Section: Discussionsupporting
confidence: 88%
“…To determine whether axotomy in vivo induces DNA binding by c-Jun, and to identif y possible partners for c-Jun in DNA binding, we investigated the effect of axotomy on the formation and composition of AP-1 binding complexes in DRGs at various times after injury, using an AP-1 consensus sequence based on the human metallothionein II A (Hmt II A ) promotor in electrophoretic mobility shift assays with antibodies to various jun family members. We did not examine DRGs for AP-1 binding by c-fos, a highly stable partner for c-Jun (Angel and Karin, 1991), because studies using various techniques have not detected this transcription factor in DRGs (Herdegen et al, 1992;Plantinga et al, 1994). ATF2, a member of the CRE-binding protein family, can dimerize with c-Jun to initiate c-Jun transcription from a specialized TRE in the c-Jun promotor (van Dam et al, 1993) but has been shown not to bind to the consensus AP-1 sequence used in our study (Hai and Curran, 1991).…”
Section: Ap-1 Binding Activity Is Induced In Axotomized Drgsmentioning
confidence: 99%